Trans (elaidic) fatty acids adversely affect the lipoprotein profile relative to specific saturated fatty acids in humans - Sundram, K; Ismail, A; Hayes, K.C; Jeyamalar, R; Pathmanathan, R (The Journal of nutrition, 1997)
Although dietary trans fatty acids can affect plasma lipoproteins negatively in humans, no direct comparison with specific saturated fatty acids has been reported, even though trans fatty acids were designed to replace saturates in foods and food processing. In this study, dietary trans 18:1 [elaidic acid at 5.5% energy (en)] was specifically exchanged for cis 18:1, 16:0 or 12:0 + 14:0 in 27 male and female subjects consuming moderate fat (31% en), low cholesterol (225 mg/d) whole food diets during 4-wk diet periods in a crossover design. The trans-rich fat significantly elevated total cholesterol and LDL cholesterol relative to the 16:0-rich and 18:1-rich fats and uniquely depressed HDL cholesterol relative to all of the fats tested. Trans fatty acids also elevated lipoprotein (a) [Lp(a)] values relative to all dietary treatments. Furthermore, identical effects on lipoproteins were elicited by 16:0 and cis 18:1 in these subjects. The current results suggest that elaidic acid, one of the principal trans isomers produced during industrial hydrogenation of edible oils, adversely affects plasma lipoproteins. Thus, the negative effect of elaidic acid on the lipoprotein profile of humans appears to be unmatched by any other natural fatty acid(s)